Exposure to Daily Price Changes and Inflation Expectations - Francesco D'Acunto; Ulrike M. Malmendier; Juan Ospina; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2019)
We show that, to form aggregate inflation expectations, consumers rely on the price changes they face in their daily lives while grocery shopping. Specifically, the frequency and size of price changes, rather than their expenditure share, matter for individuals' inflation expectations. To document these facts, we collect novel micro data for a representative US sample that uniquely match individual expectations, detailed information about consumption bundles, and item-level prices. Our results suggest that the frequency and size of grocery-price changes to which consumers are personally exposed should be incorporated in models of expectations formation. Central banks' focus on core inflation - which excludes grocery prices - to design expectations-based policies might lead to systematic mistakes.
Keywords: C90; D14; D84; E31; E52; E71; G11; 330; beliefs formation; rational inattention; realized inflation; transmission of monetary policy